Multiportal Combined Transorbital and Transnasal Endoscopic Resection of Fibrous Dysplasia - Tham, Tristan; Costantino, Peter; Bruni, Margherita; Langer, David; Boockvar, John; Singh, Prabhjyot (Journal of Neurological Surgery Reports, 2015)
Introduction Historically, access to the anterior skull base was achieved with open procedures. The paradigms to this approach were challenged with the advent of minimally disruptive endoscopic surgical techniques and supporting technology. The next step in the evolution of minimally disruptive surgery was the combination of multiportal endoscopic surgery.Results The patient was an 18-year-old man who presented with right-sided proptosis. Further diagnostic tests revealed a fibrous dysplasia (FD) occupying the skull base and orbit. The lesion was successfully resected.Conclusions The location of the tumor in this case was challenging, in which surgeons at some centers would have opted to have performed as an open procedure instead of endoscopically. The combined transnasal/transorbital approach is an uncommonly used technique that we have used to remove this tumor successfully. The patient also had a unique disease (FD) in a unique location that was treated without complications. This case report highlights how surgeons may use an expanded armamentarium in dealing with complex pathologies.
Keywords: combined multiportal endoscopic skull base surgery; transnasal; transorbital